Investigation of Health Science Students' Knowledge Regarding Healthy Lifestyle Promotion During the Spread of COVID-19 Pandemic: A Randomized Controlled Trial - Alotaibi, Naser; Al-Sayegh, Nowall; Nadar, Mohammed; Shayea, Abdulaziz; Allafi, Ahmed; Almari, Mohammed (Frontiers in Public Health, 2021)
Background: Health sciences students as future health care providers, can play a valuable role in protecting societies against the spread of COVID-19 through health promotion and lifestyle modification education. Therefore, proper education of these students is essential. Objective: This study sought to assess and measure the change of knowledge of health sciences students regarding healthy lifestyle promotion strategies during the spread of the Covid-19 pandemic, after participation in different types of online and social media educational programs. Methods: In order to serve the purpose of the study, a methodological research design was first used to ensure the validation of the developed scale; the COVID-19 Healthy Lifestyle Promotion Scale (COVID-19 HLPS). The study utilized a four-arm randomized control research design in which the participants were randomly assigned into one of four groups, (1) control group (placebo intervention), (2) brochure group, who received brochures relevant to healthy lifestyle promotion, (3) Instagram group, who received similar information but through Instagram posts, and (4) online interactive educational workshop group, who also received similar information through an online interactive educational workshop. Results: In total, 155 participants participated in the online and social media intervention programs. There was a significant improvement in the intervention groups in the total knowledge subscale of the healthy promotion strategies compared with the control group (p < 0.001). Overall, the workshop group was the most effective group (effect size = 1.54) followed by the Instagram group (effect size = 0.99) and then the brochure group (effect size = 0.91). Conclusions: In order to meet the challenges posed by this pandemic, the use of such online and social media interventions is essential and may be the key for health promotion during this pandemic. Health science students, as future health care professionals, can play a fundamental role during the COVID-19 pandemic in disseminating knowledge relevant to healthy lifestyle to their families and communities thus promoting healthy living and behavioral changes. We propose the development of research initiatives at both national and international levels targeting changes within health science curricula that can meet potential challenges of future pandemics, leading to advancement of health care services globally.